A Compact Shared-Aperture Antenna With 2-Transmit and 2-Receive Highly-Isolated Ports for Full-Duplex MIMO Systems - Junhui Rao; Zhaoyang Ming; Jichen Zhang; Zan Li; Chi-Yuk Chiu; Ross Murch (IEEE Open Journal of Antennas and Propagation)
In-band full-duplex (IBFD) antennas have been proposed for next-generation wireless communication as they can increase system throughput by up to two times. In this work, a compact multiple-input multiple-output (MIMO) IBFD antenna featuring two co-polarized transmit (Tx) ports and two co-polarized receive (Rx) ports is proposed that is suitable for use in mobile devices. The design is one of the first to include MIMO into IBFD antennas. The fabricated and measured proposed antenna exhibits over 32 dB self-interference (SI) isolation between Tx and Rx ports and less than −18.2 dB mutual-coupling (MC) within Tx and Rx pairs. All radiation patterns are in the broadside direction and it operates in the 2.5 GHz frequency band. A novel “inverted mushroom” (IMR) structure, composed of a metallic pillar fence connecting two layers of optimized metal tiles, is introduced at the antenna’s center to suppress the Tx ports MC and ensure effective radiation for Rx ports. Additionally, an analytical method is proposed to optimize the IMR for achieving the desired performance. To integrate all four ports within a single antenna aperture of $0.38λ × 0.38λ × 0.11λ $ , polarization-dependent “teeth-like” gaps are proposed to protect Tx ports from IMR influence while maintaining the normal operation of Rx ports. Moreover, differential feeding networks are designed to enhance the SI isolation between Tx and Rx ports.